Cameos from the Archaeological Museum of Istria (Archaeologia Adriatica, 2022)
The paper deals with four cameos from the Archaeological Museum of Istria. One of them portrays the Emperor Nero, two bear portrayals of female heads with Greek hairstyle, and the fourth one depicts helmeted Minerva’s head. On the basis of motifselection, rendering, and comparisons with published cameos from other collections, we can assume their broad dating and analyze their messages. Cameo with Nero’s portrait can be associated with the workshop center in Rome. It is not possible to establish the workshop center where other cameos were produced.